MODAL SOSIAL IBU HAMIL DALAM PROGRAM PENDAMPINGAN KADER - Ani Sukarsih Ani Sukarsih; Pulung Siswantara Pulung Siswantara (Universitas Airlangga, 2017)
Assistance for pregnant mother is one out of many government's programs to reduce Maternal Mortality Rate (or MMR) and Infant Mortality Rate (or IMR). This program is being particularly focused on high-risk group of pregnant mothers, is a kind of fi eld activity to improve the welfare of the mother. Assistance itself in the implementation can not be separated from social capital. Assistance provided to pregnant mothers by health cadres itself is a manifestation of active roles in the community in which the cadres play continuous role in interaction. The purpose of this study was to analyze social capital in 'assistance for pregnant mother' program. The study applied cross-sectional study design with a quantitative approach on as many as 35 pregnant mothers who were included in "assistance for pregnant mother" in Surabaya. Sampling was carried out using cluster random sampling. The independent variables were the confi dence, norms and network while the dependent one was assistance for pregnant mother. Data analysis was performed using Spearman correlation test. The results showed that as many as 21 respondents (or 60.0%) had high levels of social capital, 20 respondents (57.1%) had a moderate level of trust towards the cadres as a mentor, 29 respondents (82.9%) thought to have owned norms that were supporting assistance for pregnant mother and 14 respondents (40.0%) thought that their networks were supporting the assistance. Spearman test indicated that no relationship was existed between social capital and assistance for pregnant mother, elements in social capital that had a relationship with the assistance for pregnant mother were the trust and norms. Keywords: Social capital, Assistance program, pregnant mother